On approximation of a weighted Lipschitz class functions by means tn(f; x), N?n (f; x) and R?n(f, x) of Fourier series - Jafarov, S.Z. (Institute of Mathematics and Mechanics, National Academy of Sciences of Azerbaijan, 2020)
In this work the approximation properties of the functions by means tn(f; x), N?n (f; x) and R?n(f, x) of the trigonometric Fourier series in weighted Lebesgue spaces with variable exponent are investigated. © 2020, Institute of Mathematics and Mechanics, National Academy of Sciences of Azerbaijan. All rights reserved.
Keywords: Modulus of continuity; Trigonometric approximation; Weighted Lebesgue spaces with variable exponent; Weighted Lipschitz class